Risk dynamics surrounding the issuance of convertible bonds - Zeidler, Felix; Mietzner, Mark; Schiereck, Dirk (Journal of Corporate Finance, 2012)
This paper analyzes the risk dynamics surrounding convertible bond offerings (CBOs) and Seasoned Equity Offerings (SEOs). As convertible bonds are commonly believed to be very effective at mitigating adverse selection or overinvestment problems we would expect differing risk and return patterns for convertible bond and seasoned equity issuers. By analyzing 1148 convertible bond offerings and comparing them to 2905 seasoned equity offerings, we show however that for both issuer types the systematic risk increases prior to issuance and drops sharply thereafter. This result is consistent with the notion of exercising real options, as growth options are always riskier than the underlying assets and exercising them at issuance causes an immediate drop in risk. The real option framework and the proposed dynamics of systematic risk also provide a rational explanation for the negative announcement effect, as well as any long-term underperformance subsequent to the CBO and the SEOs.